2022
DOI: 10.3390/jcm11020285
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Hemodialyzed Patients after SARS-CoV-2 Infection

Abstract: Introduction: The determinants of COVID-19 mortality are well-characterized in the general population. Less numerous and inconsistent data are among the maintenance hemodialysis (HD) patients, who are the population most at risk of an unfavorable prognosis. Methods: In this retrospective cohort study we included all adult HD patients from the Pomeranian Voivodeship, Poland, with laboratory-confirmed SARS-CoV-2 infection hospitalized between 6 October 2020 and 28 February 2021, both those who survived, and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The COVID-19 Task Force Team not only published a COVID-19 prevention guideline [8] but also proposed adequate vaccination and treatment policies to the KDCA, which resulted in lower rates of disease incidence and mortality among HD units [15]. Previous studies have suggested the proportion of asymptomatic SARS-CoV-2 infection among HD patients is approximately 25% [16,17]. Our study demonstrated a higher prevalence of asymptomatic infection (33.9%) compared to previous studies.…”
Section: Discussionmentioning
confidence: 48%
“…The COVID-19 Task Force Team not only published a COVID-19 prevention guideline [8] but also proposed adequate vaccination and treatment policies to the KDCA, which resulted in lower rates of disease incidence and mortality among HD units [15]. Previous studies have suggested the proportion of asymptomatic SARS-CoV-2 infection among HD patients is approximately 25% [16,17]. Our study demonstrated a higher prevalence of asymptomatic infection (33.9%) compared to previous studies.…”
Section: Discussionmentioning
confidence: 48%
“…The predictive value of inflammation level and lymphopenia concerning the progression of COVID-19 and a poor outcome was reported in previous studies [ 20 , 38 ]. In our recent study, high CRP and D-dimer levels upon admission were strongly associated with a 3-month mortality risk in HD patients [ 39 ]. Other studies also show a predictive value of blood oxygenation indices for the severity of pneumonia and mortality of COVID-19 patients [ 21 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, research into vitamin D supplementation in the prevention and treatment of COVID-19 provides inconsistent results [ 48 , 49 ]. In the recent study, we originally found that in HD patients who were treated with active vitamin D, there may be a lower risk of 3 month death from COVID-19 [ 39 ]. There was substantial clinical and methodological heterogeneity of the conducted studies, mainly because of different supplementation strategies, formulations, vitamin D status of participants, and reported outcomes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, although both analyzes were performed in the same dialysis centers and the two cohorts mostly overlap, they were not the same. Therefore, it cannot be excluded that the results of the study may be influenced by the fact that the patients with the greatest frailty and worst prognosis have died during the first waves of the pandemic and were no longer on dialysis during the second study period ( 15 ). Finally, due to the nature of the data register, we did not have individual patient data that would allow us to compare the characteristics of the vaccinated and non-vaccinated groups and perform any multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%